Amplifying endogenous stem cell migration for in situ bone tissue formation: Substance P analog and BMP mimetic peptide-loaded click-crosslinked hyaluronic acid hydrogel - Kim, Hee Eun; Ju, Hyeon Jin; Kim, Shina; Kim, Young Hun; Lee, Soyeon; Choi, Sangdun; Yoon, Hyun C.; Choi, Hak Soo; Kim, Moon Suk (Materials Today Bio, 2024)
Endogenous stem cell-driven in situ bone tissue formation has recently garnered increasing attention. Therefore, our study sought to refine methods to enhance the migration and subsequent osteogenic differentiation of these cells. Our innovative approach involves using an injectable hydrogel that combines click cross-linking sites and a BMP-2 mimetic peptide (BP) with hyaluronic acid (HA). This injectable formulation, hereinafter referred to as SPa + Cx-HA-BP, incorporates a substance P analog peptide (SPa) with Cx-HA-BP, proving versatile for in vitro and in vivo applications without cytotoxicity. The controlled release of SPa creates a gradient that guides endogenous stem cells towards the Cx-HA scaffold from specific tissue niches. Both Cx-HA and SPa+Cx-HA induced minimal changes in the expression of genes associated with osteogenic differentiation. In contrast, these genes were robustly induced by both SPa + Cx-HA+BP and SPa + Cx-HA-BP, in which BP was respectively integrated via physical and chemical methods. Remarkably, chemically incorporating BP (Cx-HA-BP) resulted in 4–9 times higher osteogenic gene expression than physically mixed BP in Cx-HA+BP. This study validates the role of SPa role in guiding endogenous stem cells toward the hydrogel and underscores the substantial impact of sustained BP presence within the hydrogel. Collectively, our findings offer valuable insights for the development of innovative strategies to promote endogenous stem cell-based tissue regeneration. The developed hydrogel effectively guides stem cells from their natural locations and facilitates sustained osteogenic differentiation, thus holding great promise for applications in regenerative medicine.
Keywords: BMP-2 mimetic peptide; Bone tissue formation; Cell migration; Crosslinked; Endogenous stem cells; In situ osteogenic differentiation; Mimetics; Osteogenic differentiation; Substance P analog peptide; Substance-P; BMP-2 mimetic peptide; Endogenous stem cell; Hyaluronic acid; In situ osteogenic differentiation; Scaffold; Substance P analog peptide